ETHNIC IDENTITY AND LAND UTILIZATION: A CASE STUDY IN RIAU, INDONESIA - Joan Hardjono (Kedeputian Bidang Ilmu Sosial dan Kemanusiaan (IPSK-LIPI), 2013)
This article looks at the economic and social position of first- and second- generationtransmigrants of Javanese origin in the northwestern part of the Province of Riau,Sumatra, in the aftermath of the 1997/98 monetary crisis. The article is based on thefindings of a study undertaken by the author in 2001 in the context of the InternationalLabour Organization's InFocus Programme on Socio-Economic Security calledIndonesia: Improving Security After the Crises. Data were collected in two villagesin a transmigration settlement near Pasir Pangarayan, Riau, where several thousandtransmigrant families had been resettled during the 1980s.Keywords: Ethnic identity, Transmigrants, Land use, Labour, Palm oil, Riau